1992
DOI: 10.1042/bj2820723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamine depletion on chromatin structure in U-87 MG human brain tumour cells

Abstract: The chromatin structure of polyamine-depleted U-87 MG human brain tumour cells was studied by following the kinetics of digestion of cell nuclei by micrococcal nuclease and bovine pancreatic DNAase I. Cells growing in monolayers were treated with either alpha-difluoromethylornithine (DFMO), to deplete putrescine and spermidine, or N1,N14-bis(ethyl)homospermine (BE-4-4-4), to deplete putrescine, spermidine and spermine. BE-4-4-4 increased the initial rates of digestion and the magnitudes of limit digest by both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…However, the increased expression of SSAT is only observed in the presence of analogue or natural polyamines, suggesting that the activity of Nrf-2 is altered in the presence of the cation. Basu et al (41,42) have demonstrated profound changes in DNA conformation in the presence of the polyamine analogues. It has also been shown that DNA/protein interactions can be altered by the natural polyamines, as demonstrated by examining the effects of polyamines on restriction FIG.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased expression of SSAT is only observed in the presence of analogue or natural polyamines, suggesting that the activity of Nrf-2 is altered in the presence of the cation. Basu et al (41,42) have demonstrated profound changes in DNA conformation in the presence of the polyamine analogues. It has also been shown that DNA/protein interactions can be altered by the natural polyamines, as demonstrated by examining the effects of polyamines on restriction FIG.…”
Section: Discussionmentioning
confidence: 99%
“…DNA topoisomerase II levels were unchanged after treatment with MAP/AbeAdo. The third explanation seems the most likely, considering that changes in polyamine levels may modify the activity of other DNA-processing enzymes (Basu et al, 1992) and are believed to affect the DNA binding of transcription factors (Celano et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine depletion has been shown to alter the state and structure of chromatin (Snyder, 1989;Basu et al, 1992) and this may affect the DNA replication apparatus. Polyamines have also been shown to directly stimulate the activity of DNA polymerases (Hironaka et al, 1987;Bachrach and Abu-Elheiga, 1990).…”
Section: Discussionmentioning
confidence: 99%